Towards an Efficient Algorithm to Get the Chorus of a Salsa Song (2016)
A well-known musical genre and part of Latin-American cultural identity is Salsa. To be able to perform a scientific analysis of this genre, the first step to take is to analyze the structure of Salsa songs. Furthermore, the most representative part of Salsa is the chorus. In this paper we detail the design and implementation of an algorithm developed for getting the chorus of any Salsa song.